Ammonia-Oxidizing Archaea (AOA) Play with Ammonia-Oxidizing Bacteria (AOB) in Nitrogen Removal from Wastewater. (13th September 2018) - Yin, Zhixuan; Bi, Xuejun; Xu, Chenlu
Abstract : An increase in the number of publications in recent years indicates that besides ammonia-oxidizing bacteria (AOB), ammonia-oxidizing archaea (AOA) may play an important role in nitrogen removal from wastewater, gaining wide attention in the wastewater engineering field. This paper reviews the current knowledge on AOA and AOB involved in wastewater treatment systems and summarises the environmental factors affecting AOA and AOB. Current findings reveal that AOA have stronger environmental adaptability compared with AOB under extreme environmental conditions (such as low temperature and low oxygen level). However, there is still little information on the cooperation and competition relationship between AOA and AOB, and other microbes related to nitrogen removal, which needs further exploration. Furthermore, future studies are proposed to develop novel nitrogen removal processes dominated by AOA by parameter optimization.